Concentrated Lithium Dodecyl Sulfate Aqueous Electrolytes: Utilizing Self‐Assembly and Interfacial Adsorption for Aqueous Li‐ion Batteries. Issue 20 (17th October 2022) - Kondou, Shinji; Morinaga, Asuka; Hashimoto, Kei; Katayama, Yu; Dokko, Kaoru; Watanabe, Masayoshi; Ueno, Kazuhide
Abstract: Since aqueous lithium‐ion batteries (LIBs) were first proposed, electrolyte design has been intensively studied. We report a simple anionic surfactant, i. e., a lithium dodecyl sulfate (LiDS)‐based aqueous electrolyte, capable of enhancing the Li ion transport properties in the bulk and protecting the electrode at the interface. The self‐assembly of DS anions into micelles effectively limited anion diffusion, enabling nearly single Li‐ion conduction in the bulk electrolyte. The interfacial adsorption of DS molecules formed a hydrophobic layer at the electrolyte/electrode interface under the electric field of the electric double layer, excluding water molecules from the interface. Consequently, the electrochemical window of the aqueous electrolyte was expanded to 3.0 V. This electrolyte improved the cycle performance and rate capability of the LiFePO4 /LiTi2 (PO4 )3 full‐cell compared to a 1.0 mol dm −3 Li2 SO4 /H2 O reference electrolyte. These results provide a new twist in the design of liquid electrolytes for aqueous LIBs. Abstract : Aqueous Electrolytes for Batteries : The self‐assembly of lithium dodecyl sulfate (LiDS) into micelles effectively limited anion diffusion, enabling nearly single Li‐ion conduction in the bulk electrolyte. The DS molecules formed a hydrophobic layer at the interface under the electric field, expanding the electrochemical window to 3.0 V. This electrolyte enabled good battery performance of the LiTi2 (PO4 )3 /LiFePO4 full‐cell.